Change in surface energy balance in Alaska due to fire and spring warming, based on upscaling eddy covariance measurements. Issue 10 (9th October 2014) - Ueyama, Masahito; Ichii, Kazuhito; Iwata, Hiroki; Euskirchen, Eugénie S.; Zona, Donatella; Rocha, Adrian V.; Harazono, Yoshinobu; Iwama, Chie; Nakai, Taro; Oechel, Walter C.
Abstract Warming in northern high latitudes has changed the energy balance between terrestrial ecosystems and the atmosphere. This study evaluated changes in regional surface energy exchange in Alaska from 2000 to 2011 when substantial declines in spring snow cover due to spring warming and large‐scale fire events were observed. Energy fluxes from a network of 20 eddy covariance sites were upscaled using a support vector regression (SVR) model, by combining satellite remote sensing data and global climate data. Based on site‐scale analysis, SVR reproduced observed net radiation, sensible heat flux, latent heat flux, and ground heat flux; 8 day root‐mean‐square errors for these variables were 15, 10, 9, and 3 W m−2, respectively. Based on upscaled fluxes, decreases in spring snow cover induced an increase in surface net radiation, a net heating effect, of 0.56 W m−2 decade−1. This heating effect was comparable to the net cooling effect due to increased fire extent during the study period (up to 0.59 W m−2 decade−1). These land cover effects were larger than the change in the energy forcing associated with CO2 balance for the Alaska region. Spring warming and postfire land cover change increased the regional latent heat flux. The regional sensible heat flux decreased with the postfire land cover change. Our results highlight the importance of positive spring snow albedo feedback to climate and a postfire negative feedback under the expected warming climate in the Arctic.